The tall pine polka - Landvik, Lorna, frey50 (New York : Ballantine Books, 1999)
A film shoot brings romantic intrigue to the woods of Minnesota. Fenny Ness who runs the bait shop is hired to star in the movie, which attracts the attention of Big Bill, a half-Indian musician. Which in turn provokes jealousy in the redhead who runs the local diner. By the author of Your Oasis on Flame Lake.
84472
Keywords: Coffee shops -- Fiction; Motion picture industry -- Fiction; Minnesota -- Fiction; Pastoral fiction